APPLICATION OF THE KODALY METHOD IN ANGKLUNG MUSIC LEARNING USING THE CONCEPT OF BERKAWAN AND KAWAN BERKAWAN - Irawan Sukma (JURNAL PAKARENA, 2022)
Currently, angklung music has become part of ensemble music that can be taught to students at the elementary, middle, and high school levels as a form of appreciation for traditional Indonesian music. Therefore, through this research, the technique of playing angklung will be developed with the Kodaly method with the concept of Berkawan and Kawan Berkawan so that later it can display a form of musical presentation packaged in the form of a similar music ensemble. This research is qualitative, using the Research and Development approach from Borg and Gall, by discussing matters related to melody science, the laws of harmony in songs applied in choirs, tone symbols (the use of fingers), the Kodaly method with the development of the concept of Berkawan and Kawan Berkawan, and song notation. The initial stage is the observation of the Kodaly Method, then analyzing the shape of the Kodaly Method symbol with the application of the concept of Berkawan and Kawan Berkawan, then trying to apply it to several grade VII students of SMP Negeri Belitang Jaya from these methods and concepts. In the end, it is hoped that the Kodaly Method with the concept of Berkawan and Kawan Berkawan can be applied and taught to students as the best solution for playing Angklung Music easily. The results of this study revealed that the application of the Kodaly (hand sign) method in angklung learning can improve the ability to read notation to students and is a practical and effective method for students of SMPN 2 Belitang Jaya. It can be seen that the concept of Berkawan with two voices and Kawan Berkawan with three voices is very effective and practical in understanding the technique of playing angklung quickly. So that the application of the Kodaly method can be developed through the concept of Berkawan and Kawan Berkawan